Eco-products value realization and eco-industry design of afforestation in the Karst Desertification Control - Yu Zhang; Zefu Zhang; Kangning Xiong; Youze Ning (PLoS ONE, 2025)
Karst desertification (KD) severely restricts rural development in China’s karst regions. To ensure both ecological security and economic sustainability, afforestation is essential for karst desertification control (KDC). This paper utilizes scientific approaches, including Ecological Product (EP) value accounting (which evaluates the value of ecosystem - provided products and services for humans) and data statistical analysis, to explore the functions of afforestation in EP distribution, value realization, and Ecological Industry (EI) formation. The study reveals several key findings. (1) In the three study areas, afforestation significantly impacts the regulation of service product values. For instance, in the Shibing area, Horsetail pine is the main EP supplier; in the langyashan study area, it is cypress; and in the Zunhua study area, oil pine. (2) In the southern karst (exemplified by the Shibing study area), EP values are influenced by factors like stand height, diameter at breast height, altitude, organic carbon, and soil total nitrogen. In the northern karst (using langyashan study area and Zunhua study areas as examples), soil total nitrogen, organic carbon, and porosity are the main determinants. (3) With decreasing altitude, industrial distribution shifts from an ecological - forest - based industry to one with co - existing ecological and economic forests, and finally to an economic - forest - based industry. Rational selection and breeding of economic forest species aid in creating ecolabel brands. This small - watershed - scale analysis improves the accuracy of assessing ecological and economic development in karst areas, providing a scientific basis for decision - making to strengthen ecological restoration and enhance people’s well - being.